HUBUNGAN POLA TERAPI DENGAN KUALITAS HIDUP PASIEN TB PARU DI BALAI KESEHATAN MASYARAKAT WILAYAH PATI - Timur, Willi Wahyu; Sabiti, Farroh Bintang; Amajida, Neva Linsya (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Tuberculosis (TB) until 2018 has been a major global health issue, with an annual incidence rate of 9 million cases worldwide and contributing to up to 2 million deaths. TB falls within the top 10 diseases that can cause significant mortality worldwide. Indonesia accounts for 9.2% of these cases, ranking second in the highest number of TB cases after India. This research aims to determine the relationship between treatment patterns and the quality of life in pulmonary TB patients at the Pati District Public Health Center. Data was processed using the SPSS application with Spearman correlation analysis. The study involved 50 respondents diagnosed with pulmonary TB. The independent variable was the treatment pattern of pulmonary TB patients measured using the patient's treatment phase, while the dependent variable was the quality of life measured using the SF-36 Quality of Life Questionnaire. Results from 20 respondents in the intensive phase show that 6 (30.0%) individuals had good quality of life, while 14 (70.0%) individuals had poor quality of life. In the advanced phase, with 30 respondents, 7 (23.3%) had low quality of life, while 23 (76.7%) had good quality of life. The p-value was found to be 0.001, indicating a significant relationship between the treatment pattern and the quality of life in pulmonary TB patients at the Pati District Public Health Center.